(untitled) (Research, Society and Development, 2023)
The cosmetics consumption has acquired new aspects along social and scientific progress and the consequent greater access to information. The search for a sustainable lifestyle has formed the "green consumer", responsible for stimulating the repositioning of companies related to formulation of beauty products and application of sustainability in their production models, which led to the creation of the "green cosmetics”, -which covers organic, natural, and vegan cosmetics. The main goal of this work was to carry out a systematic literature review about the sustainable trend in cosmetics development, considering the use of natural ingredients in products formulation and the challenges resulting from cosmetics development and packaging in a sustainable way; issues related to the legislation and certification of these products and the behavior of companies in the execution of competitive strategies to follow this movement. For this, the research was accomplished according to the keywords in databases such as Scielo, PubMed, ResearchGate and Google Scholar, in addition to publications in relevant journals in the segment of interest. Based on the data presented in this study, it is evident that the considered trend has become a solid practice in the beauty sector, creating a market concerned with its environmental performance in the face of society’s new desires; even so, because it remains in constant evolution, as well as its consumers, this practice presents some significant obstacles, making a critical analysis based on the exposed considerations necessary.